The implementation of e-commerce dynamic rate to generate room revenue - Putu Rian Arde Surya; Dewa Made Suria Antara; Ni Gst Nym Suci Murni; Ni Luh Ayu Kartika Yuniastari Sarja (International Journal of Green Tourism Research and Applications, 2019)
This study aims to determine the e-commerce dynamic rate structure to generate room revenue and the better implementation between dynamic rate and the static rate at a 3 star hotel in Kuta, Bali. Data collection methods used in this research as follows: interviews, observation, and documentation. The data analysis technique used is the mean analysis technique, dynamic pricing method, profit margin ratio, and descriptive analysis techniques. The results of the study showed the step by step of dynamic rate structure determination and the dynamic rate is better than the static rate. This is indicated by the results of the average profit margin ratio in 2016-2018 on the dynamic rate at 39.41% compared to the static rate at 2.00%. Based on the results of the analysis, any efforts that can be made are paying attention to the dynamic rate during decreasing the Price Points (PP), thus avoiding complaints from offline travel agents and implement the dynamic rates for offline travel agents, hence generate profits with a greater profit margin ratio for the hotel